Advances in understanding chromosome silencing by the long non-coding RNA Xist - Sado, Takashi (The Royal Society, 2013)
In female mammals, one of the two X chromosomes becomes genetically silenced to compensate for dosage imbalance of X-linked genes between XX females and XY males. X chromosome inactivation (X-inactivation) is a classical model for epigenetic gene regulation in mammals and has been studied for half a century. In the last two decades, efforts have been focused on the X inactive-specific transcript (Xist) locus, discovered to be the master regulator of X-inactivation. The Xist gene produces a non-coding RNA that functions as the primary switch for X-inactivation, coating the X chromosome from which it is transcribed in cis. Significant progress has been made towards understanding how Xist is regulated at the onset of X-inactivation, but our understanding of the molecular basis of silencing mediated by Xist RNA has progressed more slowly. A picture has, however, begun to emerge, and new tools and resources hold out the promise of further advances to come. Here, we provide an overview of the current state of our knowledge, what is known about Xist RNA and how it may trigger chromosome silencing.